2022
DOI: 10.3389/fnins.2022.868088
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Extract, but Not Electronic Cigarette Aerosol Extract, Inhibits Monoamine Oxidase in vitro and Produces Greater Acute Aversive/Anhedonic Effects Than Nicotine Alone on Intracranial Self-Stimulation in Rats

Abstract: Conventional tobacco cigarettes appear to have greater abuse liability than non-combusted products such as electronic cigarettes (ECs) and nicotine replacement therapy (NRT). This may be due to the higher levels of behaviorally active non-nicotine constituents [e.g., monoamine oxidase (MAO) inhibitors such as β-carbolines] in cigarette smoke (CS) compared to non-combusted products. To evaluate this hypothesis, the current studies compared the relative abuse liability of CS and EC aerosol extracts containing ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…Although substantial work has been done on the identity of non-nicotine constituents that impact nicotine reinforcement and reward [ 24 , 26 , 58 62 ], there are few studies that have looked at the impact of individual constituents on nicotine withdrawal. One exception is monoamine oxidase inhibitors (MAOIs) in tobacco which reduce enzyme activity in the brains of smokers [ 63 ] and are present in CSE extracts [ 24 , 64 ]. In rats, chronic MAOI treatment induces a prolonged conditioned placed aversion associated with nicotine withdrawal [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although substantial work has been done on the identity of non-nicotine constituents that impact nicotine reinforcement and reward [ 24 , 26 , 58 62 ], there are few studies that have looked at the impact of individual constituents on nicotine withdrawal. One exception is monoamine oxidase inhibitors (MAOIs) in tobacco which reduce enzyme activity in the brains of smokers [ 63 ] and are present in CSE extracts [ 24 , 64 ]. In rats, chronic MAOI treatment induces a prolonged conditioned placed aversion associated with nicotine withdrawal [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have confirmed that non-nicotine tobacco constituents in CSE administered intravenously enhance both physical and affective symptoms of nicotine withdrawal in adult rats. We have previously shown that these constituents do not impact nicotine self-administration, but do enhance reinstatement induced by the pharmacological stressor, yohimbine [ 24 , 27 ] and elevate and increase intracranial self-stimulation thresholds to a greater degree than high doses of nicotine alone [ 64 ]. Thus, tobacco constituents appear to increase the negative impact of withdrawal from chronic nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring β-carboline alkaloids have been identified in the inhibition of MAO by cigarette smoke [ 21 , 22 ], coffee [ 23 ] and raisins [ 24 ]. The inhibition of MAO in smokers and coffee drinkers might be linked with some biological actions, such as the addictive properties of cigarettes and depression [ 25 , 26 ] and the lowest incidence of Parkinson’s disease (PD) [ 27 , 28 , 29 , 30 ]. More research is currently needed to study the effects of diet and environmental factors on MAO enzymes.…”
Section: Introductionmentioning
confidence: 99%